2005
DOI: 10.1002/jsfa.2050
|View full text |Cite
|
Sign up to set email alerts
|

Effects of germination conditions on ascorbic acid level and yield of soybean sprouts

Abstract: The effects of light illumination on the ascorbic acid content and growth of soybean sprouts were investigated. Among the six light qualities studied, ultraviolet light had the highest promoting effect on the ascorbic acid content in soybean sprouts, increasing it by 77.0% compared with the darkness control, while red light had the highest promoting effect on the growth of soybean sprouts, increasing the total fresh weight by 16.6% compared with the darkness control. Experiments with different durations of ult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
66
1
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(81 citation statements)
references
References 20 publications
(19 reference statements)
10
66
1
4
Order By: Relevance
“…This result was in accordance with that published by Lintschinger et al [17] for 3 days-germinated quinoa seeds. The effect of germination on the vitamin C levels has also been observed in other grains such as wheat, buckwheat, chickpea, lupin and soybean [16][17][18][19], indicating that the biosynthesis of vitamin C is a specific metabolic process during germination which seems to be directly implicated in the modulation of initial embryo germination and plant growth, protecting other biological substances from oxidative damage [16]. In contrast to germination, the vitamin C present in raw quinoa disappeared completely after either induced or spontaneous fermentation.…”
Section: Resultsmentioning
confidence: 90%
“…This result was in accordance with that published by Lintschinger et al [17] for 3 days-germinated quinoa seeds. The effect of germination on the vitamin C levels has also been observed in other grains such as wheat, buckwheat, chickpea, lupin and soybean [16][17][18][19], indicating that the biosynthesis of vitamin C is a specific metabolic process during germination which seems to be directly implicated in the modulation of initial embryo germination and plant growth, protecting other biological substances from oxidative damage [16]. In contrast to germination, the vitamin C present in raw quinoa disappeared completely after either induced or spontaneous fermentation.…”
Section: Resultsmentioning
confidence: 90%
“…Five-day germination of white beans increased the ascorbic acid content by 300% [7]. 43 Mediterr J Nutr Metab (2010) 3:39-46 After 3 days of soybean germination, the vitamin C levels reached 25 mg per 100 g dry seeds [25], while Xu et al [34] observed a level of 26.3 mg per 100 g dry seeds after a day of soy germination.…”
Section: Vitaminsmentioning
confidence: 96%
“…Germination generally improves the nutritional quality of foods by increasing their nutrient content and digestibility. The content of vitamin C is particularly enhanced during the process of germination (Xu, Dong, & Zhu, 2005). Germination can bring about a twofold increase in bioavailability of iron, whereas malting of minor millets brings about a 5-to 10-fold increase in the same (Tontisirin, Nantel, & Bhattacharjee, 2002).…”
Section: Introductionmentioning
confidence: 99%